2012
DOI: 10.12693/aphyspola.121.1321
|View full text |Cite
|
Sign up to set email alerts
|

Physical Properties of Magnetite Nanoparticles Covered by 11-Mercaptoundecanoic Acid

Abstract: We have investigated the magnetic behavior of magnetite nanoparticles covered by the 11-mercaptoundecanoic acid around magnetite core prepared by a standard co-precipitation method. The particles show superparamagnetic behavior at room temperature, with transition to a blocked state at blocking temperature 91 K estimated from zero eld cooled and eld cooled at 500 Oe experiment. The hysteresis loop measured at 293 K showed magnetization 32.8 emu/g at 50 kOe without any coercivity. The mean particle size (7.1 nm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 10 publications
1
1
0
Order By: Relevance
“…This means that the desired absorbent surface has a positive charge at pHs less than 8.50 and a negative charge at pHs greater than 8.50. This value is very close to the zpc of the Fe3O4 [85].…”
Section: Thermal Analysissupporting
confidence: 71%
“…This means that the desired absorbent surface has a positive charge at pHs less than 8.50 and a negative charge at pHs greater than 8.50. This value is very close to the zpc of the Fe3O4 [85].…”
Section: Thermal Analysissupporting
confidence: 71%
“…MUA has been used as the self-assembly reagent for preparing carboxylated noble metal nanoparticles [32] and is suitable for preparing other carboxylated nanoparticles. A previous research suggested that MUA forms a shell-layer around a non-noble-metal nanoparticle [33], the MUA might be attached to PBNPs by an electrostatic linkage. The negative charged functional groups of MUA could be linked to the exposed Fe 2+ or Fe 3+ on the PBNPs.…”
Section: Resultsmentioning
confidence: 99%